Quantifying damage level to concrete specimens - Teoh, Chun Wei. (2013)
Concrete is widely used in Singapore. Loading on concrete will induced micro-cracks, which are invisible to naked eyes, in the concrete. The propagation of micro-cracks might lead to failure of concrete and might cause disaster in the worst case scenario. Hence, study of the behavior of micro-cracks with respect to damage level of concrete is important to predict the failure mode of concrete.